Tackling Gender poverty relations within Households through micro-credit Programs in Uganda - Busingye, John (Advances in Social Sciences Research Journal, 2019)
The study mainly set out to investigate the factors that influence gender relations in Uganda. This paper contributes to the body of knowledge by determining the local gender context influencing gender poverty relations in the face of micro-credit programs and practices in Uganda. The study was grounded on the feminist conflict theory. Women accessing and utilizing microcredit programs from Savings and Credit Cooperative Organizations (SACCOs) in Mbarara (MM) and Bushenyi-Ishaka Municipalities (BIM) of South West Uganda provided the contextual setting of the study. Data was collected from a total of 198 respondents by use of interviews and focused group discussions. The study findings show that age, women’s marital status, the level of formal education, number of children depending on women, assets for collateral and signature requirements were the main factors influencing gender poverty relations within households in Uganda. The study contends that poverty and gender relations influence access to microcredit programs. The study then recommends that SACCOS should formulate gender inclusive strategies like alternative means of collateral and introduce women friendly modes of access to microcredit services as a strategy for tackling poverty among women in Uganda. The government is also advised to sensitize the public about gender poverty relations, human rights and increasing household income using the available media.